2014
DOI: 10.1007/s10708-014-9566-6
|View full text |Cite
|
Sign up to set email alerts
|

Green economy and development in small urban municipalities: towards sustainable community development

Abstract: Many Canadian localities have put in place economic development strategies and environmental action plans to promote economic prosperity and community sustainability. This paper reports on a survey on green economy and development of environment and economic development professionals and practitioners from two small urban municipalities (SUMs) in Ontario, namely: Orillia and North Bay. This research adopted a 'sustainable community development model' as a framework to explore community efforts (local initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Silva et al [17] stated that major concerns in sustainable smart cities can include carbon footprint, waste management, sustainability and cost of reduction. Fenton et al [18] introduced processes for energy and climate strategy development in Swedish municipalities with systematic stakeholder involvement, while Turvey [19] emphasized that understanding the relationship between sustainability and local development strategies is crucial for implementing such. De Vidovich et al [20] identified key issues in developing valuable conditions for organizational and financial sustainability, whereas collaboration between different actors is crucial.…”
Section: State Of Researchmentioning
confidence: 99%
“…Silva et al [17] stated that major concerns in sustainable smart cities can include carbon footprint, waste management, sustainability and cost of reduction. Fenton et al [18] introduced processes for energy and climate strategy development in Swedish municipalities with systematic stakeholder involvement, while Turvey [19] emphasized that understanding the relationship between sustainability and local development strategies is crucial for implementing such. De Vidovich et al [20] identified key issues in developing valuable conditions for organizational and financial sustainability, whereas collaboration between different actors is crucial.…”
Section: State Of Researchmentioning
confidence: 99%
“…İmalat sektöründe bütünleşik sürdürülebilirlik ve yeşil tedarik zincirinin etkileri hakkında yöneticiler ve araştırmacılara öneriler sunulmuştur. Turvey (2015) çalışmasında, Kanada Ontario'daki belediyeden çevre ve ekonomik kalkınma uzmanlarına yapılan anketin analiziyle yeşil ekonomi ve gelişimi ile ilgili bir rapor hazırlamaktır. Söz konusu çalışmada, sürdürülebilirlik kalınma ve yeşil tedarik zincirini geliştirmek için yerel girişimleri ortaya koyan sürdürülebilir topluluk kalkınma modeli kullanılmıştır.…”
Section: Li̇teratür öZeti̇unclassified
“…In global terms, UNEP (2011) defined a 耶green economy爷 in its simplest for as one that is low carbon resource efficient and socially inclusive. A green economy is seen as 野an economic activity with the goal of reducing energy consumption and improving environmental quality冶 (Turvey, 2014;Chapple, 2011). While green development is not exactly the same as a green economy, the two are related in terms of their shared focus and objective of moving towards sustainable community development and 耶greening the local economy爷 (Turvey, 2014).…”
mentioning
confidence: 99%
“…A green economy is seen as 野an economic activity with the goal of reducing energy consumption and improving environmental quality冶 (Turvey, 2014;Chapple, 2011). While green development is not exactly the same as a green economy, the two are related in terms of their shared focus and objective of moving towards sustainable community development and 耶greening the local economy爷 (Turvey, 2014). The term 野green development冶 is used in this study.…”
mentioning
confidence: 99%